2020
DOI: 10.4103/jips.jips_402_19
|View full text |Cite
|
Sign up to set email alerts
|

Utility versus futility of facebow in the fabrication of complete dentures: A systematic review

Abstract: Aim: The aim of this review was to investigate utility or futility of facebow for fabrication of complete denture prosthesis to maximise clinical efficiency and acceptability of complete dentures. Settings and Design: Systematic review following PRISMA guidelines. Materials and Methods: A study question was designed based on PICOT model which was used to evaluate whether facebow transfer is required or not for fabrication of complete denture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Provision of Removable Complete Dentures (RCDs) is one way of restoring oral function. The fabrication of an RCD entails several steps which include diagnosis, treatment planning, impression taking and border molding, casting dental models and occlusal rim blocks, bite registration, selection and setting up of artificial teeth, denture processing, and insertion [5]. The main goal of fabricating RCD is to attain harmonious occlusion that is compatible with the stomatognathic system intended to bring back the patient's mastication, phonetics, esthetics, and improved social esteem [6].…”
Section: Introductionmentioning
confidence: 99%
“…Provision of Removable Complete Dentures (RCDs) is one way of restoring oral function. The fabrication of an RCD entails several steps which include diagnosis, treatment planning, impression taking and border molding, casting dental models and occlusal rim blocks, bite registration, selection and setting up of artificial teeth, denture processing, and insertion [5]. The main goal of fabricating RCD is to attain harmonious occlusion that is compatible with the stomatognathic system intended to bring back the patient's mastication, phonetics, esthetics, and improved social esteem [6].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that while initial eccentric tooth contacts on the articulator were reliable, occlusal adjustments might be necessary post delivery. Prakash et al [ 27 ] conducted a systematic review assessing the utility of the facebow in complete denture fabrication. The review compared facebow use against simplified techniques using anatomical landmarks and found similar clinical efficiency and patient acceptability results.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined based on data saturation. The initially targeted number of interviews to be conducted was seven (7) participants, and the final number of interviewed respondents up to data saturation was fifteen (15) participants. A strategy of purposive sampling of key informants was used to collect data in consideration of areas of their expertise.…”
Section: Selection Of Study Participantsmentioning
confidence: 99%
“…The fabrication of an RCD entails several steps which include diagnosis, treatment planning, impression taking and border molding, dental model casts, occlusal rim blocks fabrication, bite registration, selection and set up of artificial teeth, wax denture try-in, denture processing and insertion, and patient's follow-up [7]. Occlusal Rim Block (ORB), which is employed in the third stage of denture fabrication consists of a rigid, accurate, and stable denture base and a rim made of a base plate wax.…”
Section: Introductionmentioning
confidence: 99%